Matriks Metalloproteinase (MMP) sebagai Biomarker Terjadinya Perforasi pada Apendisitis Akut - Ahmad Razi Maulana Alnaz; Abdul Hakim Nasution; Aqyl Hanif Abdillah (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2020)
Background: Acute appendicitis is one cause of emergency surgery in gastroenterohepatology. Only complicated appendicitis such as perforation needs surgical treatment. There is no examination able to determine patient with acute appendicitis require a surgical treatment or conservative treatment with antibiotic today. One examination could be related to appendicitis is Matrix Metalloproteinase (MMP). This literature review aims to know the potency and sensitivity of MMP as biomarker of the risk of perforated appendicitis. Method: Artivle is made by literature review from textbook and 21 journals, with 10 main journal. The journals are obtained from search engine such as Pubmed, Cochrane, and Google Scholar. Discussion: MMP has a proteolytic activity on extracellular matrix of connective tissue which increases during inflammation. The imbalance of MMP to Tissue Inhibitor of Metalloproteinase (TIMP) in appendix causes elevated proteolysis activity that injures the wall of the appendix which serves as the pathophysiology of perforation. Expression and concentration of MMP found increased significantly on biopsies, immunohistochemistry, peritoneal effluents, and serum of patients with complicated appendicitis compared to uncomplicated appendicitis. MMP is able to distinguish complicated with noncomplicated appendicitis, but requires combination with TIMP examination to determine the complication of appendicitis. Conclusion: MMP and TIMP is potential to be a biomarker of perforated appendicitis. Suggestion: Future research to find out cut off level in appendicitis is required.